Development Financing during a Crisis : Securitization of Future Receivables - Ketkar, Suhas; Ratha, Dilip (World Bank, Washington, DC, 2014)
Mexico's Telmex undertook the first future-flow securitization transaction in 1987. From then through 1999, the principal credit rating agencies rated more than 200 transactions totaling $47.3 billion. Studying several sources, the authors draw conclusions about the rationale for using this asset class, the size of its unrealized potential, and the main constraints on its growth. Typically the borrowing entity (the originator) sells its future product (receivable) directly or indirectly to an offshore special purpose vehicle (SPV), which issues the debt instrument. Designated international customers make their payments for the exports directly to an offshore collection account managed by a trustee. The collection agent makes principal and interest payments to investors and pays the rest to the originator. This transaction structure allows many investment-grade borrowers in developing countries to pierce the sovereign credit ceiling and get longer-term financing at significantly lower interest costs. The investment-grade rating attracts a wider group of investors. And establishing a credit history for the borrower makes it easier for it to access capital markets later, at lower costs. This asset class is attractive for investors-especially buy-and-hold investors, such as insurance companies-because of its good credit rating and stellar performance in good and bad times. Defaults in this asset class are rare, despite frequent liquidity crises in developing countries. Latin American issuers (Argentina, Brazil, Mexico, and Venezuela) dominate this market. Nearly half the dollar amounts raised are backed by receivables on oil and gas. Recent transactions have involved receivables on credit cards, telephones, workers' remittances, taxes, and exports. The potential for securing future receivables is several times the current level ($10 billion annually). The greatest potential lies outside Latin America, in Eastern Europe and Central Asia (fuel and mineral exports), the Middle East (oil), and South Asia (remittances, credit card vouchers, and telephone receivables). One constraint on growth is the paucity of good collateral in developing countries. Crude oil may be better collateral than refined petroleum. Agricultural commodities are harder to securitize. Another constraint: the dearth of high-quality issuers in developing countries. Securitization deals are complex, with high preparation costs and long lead times. The ideal candidates are investment-grade entities (in terms of local currency) in sub-investment-grade countries (in terms of foreign currency). Establishing indigenous rating agencies can slash out-of-pocket costs. Developing standardized templates for certain types of securitizations might help. A master trust arrangement can reduce constraints on size. Multilateral institutions might consider providing seed money and technical assistance for contingent private credit facilities.